Comparison of intravitreal anti-VEGF agents and oral carbonic anhydrase inhibitors in the treatment of cystoid macular edema secondary to retinitis pigmentosa - Liang, Jia; Wu, Xueping; Chen, Lu; Feng, Lujia; Hei, Xiangqing; Diao, Yingying; Ji, Yuke; Zheng, Huiyan; Zou, Zhenhua; Fang, Dong; Zhang, Shaochong (Frontiers in Pharmacology, 2024)
Purpose To compare the efficacy of intravitreal antivascular endothelial growth factor (anti-VEGF) agents with oral carbonic anhydrase inhibitors (CAIs) in treating cystoid macular edema (CME) secondary to retinitis pigmentosa (RP). Methods This retrospective study analyzed 98 patients (98 eyes) with RP-CME: 47 (48.0%) received intravitreal anti-VEGF agents (Ranibizumab or Bevacizumab) and 51 (52.0%) were treated with oral CAIs (methazolamide 50 mg/day or acetazolamide 500 mg/day). Medical records were reviewed to assess best-corrected visual acuity (BCVA), central macular thickness (CMT), and intraocular pressure (IOP) at baseline and at 1, 3, 6, and 12 months post-treatment using Generalized Estimation Equations (GEE). Adverse events and risk factors influencing visual prognosis were also evaluated. Results Both groups showed significant improvement in BCVA and reduction in CMT at 1 and 3 months post-treatment compared to baseline (all p < 0.001). In the oral CAIs group, these improvements persisted until 6 months. However, by 12 months, neither group exhibited significant improvements in BCVA or CMT compared to baseline (all p > 0.05). Intragroup comparisons revealed that the oral CAIs group had significantly better BCVA and CMT improvements at 3 and 6 months than intravitreal anti-VEGF group (p < 0.001 for BCVA at 3 months, p = 0.003 for BCVA at 6 months; all p < 0.001 for CMT at both 3 and 6 months). No significant differences were found between the two groups in BCVA and CMT at 12 months or in IOP at any time point (all p > 0.05). Subgroup analysis indicated that oral acetazolamide was more effective than methazolamide in reducing CMT and improving BCVA at 3 and 6 months (p = 0.005 for BCVA at 3 months, p = 0.015 for BCVA at 6 months; p = 0.037 for CMT at 3 months, p < 0.001 for CMT at 6 months). There were no significant differences in outcomes between intravitreal Ranibizumab and Bevacizumab (all p > 0.05). Correlation analysis showed that worse BCVA at 12 months was associated with older age (r = 0.202, p = 0.046), higher baseline CMT (r = 0.353, p < 0.001), poorer baseline BCVA (r = 0.579, p < 0.001), but showed no correlation with genotype. Adverse effects from oral CAIs included tingling sensation (3.9%), altered taste (9.8%), and gastrointestinal upset (7.8%). The Ranibizumab group required an average of 3.7 ± 0.8 treatments, and the Bevacizumab group required an average of 3.8 ± 0.5 treatments over the course of 1 year without experiencing severe adverse effects. Conclusion Both intravitreal anti-VEGF agents and oral CAIs effectively improved CMT and BCVA in RP-CME patients within the first 3 months of treatment. However, oral CAIs demonstrated superior anatomic and functional improvements at 6 months. Poorer BCVA prognosis was associated with older age, higher baseline CMT, poorer baseline visual acuity. Larger, randomized clinical trials with extended follow-up periods are needed to confirm these findings.